2016
DOI: 10.1037/lhb0000207
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a conceptual model for integrating the MMPI-2-RF into HCR-20V3 violence risk assessments and associations between the MMPI-2-RF and institutional violence.

Abstract: Reflecting the need to prevent violence, structured professional judgment assessment tools have been developed specifically to assess the likelihood of future violence. These tools typically integrate data from clinical interviews and collateral records to assist in the conceptualization of violence risk, but objective psychological testing may also be useful in completing the instruments. The authors describe the advantages of using the Minnesota Multiphasic Personality Inventory-2-Restructured Form (MMPI-2-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 45 publications
5
33
0
Order By: Relevance
“…Several of these same externalizing and emotion dysregulation scales, with the exceptions of Antisocial Behaviors (RC4) and Behavior-Restricting Fears (BRF) scores, were significantly associated with having a new arrest, but only RC4 was significantly associated with IPV recidivism. The correlation findings between new arrests and MMPI-2-RF scores are consistent with Tarescavage et al (2016), who found that scales measuring emotional and externalizing dysfunction were significantly associated with future violence in a sample of psychiatric inpatients. The current findings indicate that recidivating IPV offenses, however, may be more closely related to a propensity for disobeying rules and authority (i.e., high scores on RC4; Ben-Porath & Tellegen, 2008/2011), rather than emotional and externalizing problems.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Several of these same externalizing and emotion dysregulation scales, with the exceptions of Antisocial Behaviors (RC4) and Behavior-Restricting Fears (BRF) scores, were significantly associated with having a new arrest, but only RC4 was significantly associated with IPV recidivism. The correlation findings between new arrests and MMPI-2-RF scores are consistent with Tarescavage et al (2016), who found that scales measuring emotional and externalizing dysfunction were significantly associated with future violence in a sample of psychiatric inpatients. The current findings indicate that recidivating IPV offenses, however, may be more closely related to a propensity for disobeying rules and authority (i.e., high scores on RC4; Ben-Porath & Tellegen, 2008/2011), rather than emotional and externalizing problems.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, a widely used assessment of personality and psychopathology, MMPI-2-RF, may be a useful supplement for identifying individuals’ RNR factors. Mattson et al (2012), Tarescavage, Luna-Jones et al (2014), Tarescavage et al (2016), and Sellbom et al (2008) generally showed that MMPI-2-RF scales that measure emotional and externalizing dysfunction were associated with adverse outcomes, such as failure to complete treatment and recidivism in forensic settings. As such, we expected statistically significant associations with treatment dismissal and various recidivism variables for MMPI-2-RF scores from conceptually relevant externalizing scales (Behavioral/Externalizing Dysfunction [BXD], Family Problems [FML], Juvenile Conduct Problems [JCP], Substance Abuse [SUB], Aggression [AGG], Activation [ACT], Aggressiveness [AGGR-r], and Disconstraint [DISC-r]), emotional dysfunction scales (Emotional/Internalizing Dysfunction [EID], Helplessness/Hopelessness [HLP], Self-Doubt [SFD], Inefficacy [NFC], Stress/Worry [STW], Anxiety [AXY], Anger Proneness [ANP], Behavior-Restricting Fears [BRF], Multiple Specific Fears [MSF], and Negative Emotionality/Neuroticism [NEGE-r]), and an interpersonal scale (Interpersonal Passivity [IPP]), in addition to the RC Scales previously found to be related to these outcomes by Sellbom et al (2008).…”
Section: This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Future work focused on risk assessment and management is needed to examine whether those who score high on scales that are linked to Disinhibition/Externalizing (e.g. RC4, DISC‐r) might be of particular risk for institutional misconduct and future violence 66 . It is also important to examine whether disciplinary sanctions may be less effective with individuals who yield high scores on scales associated with the BAS (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…RC4, DISC-r) might be of particular risk for institutional misconduct and future violence. 66 It is also important to examine whether disciplinary sanctions may be less effective with individuals who yield high scores on scales associated with the BAS (e.g. a combination of low RC2 and high RC9).…”
Section: Mmpi-2-rf Correctional Correlatesmentioning
confidence: 99%